Surface hardening of steel parts - Idan, Alaa Fadhil І; Akimov, O. V.; Kostyk, K. O. (Одеський національний політехнічний університет, 2017)
Development of new resource-saving and costeffective technologies of combined hardening of steel parts with a significant reduction of the process duration is an important and urgent task. Aim: The aim of the work is to create a technology for combined toughening of steel parts to provide high operational properties of the steel surface layer by intensifying the nitriding process through the laser pre-treatment of steel products. Materials and Methods: Materials for study are types of steels 40, 40Cr and 38Cr2MoAl. Laser treatment of steel was performed at the LATUS-31 installation. Nitriding carried out in the environment of fine nitrogen-containing substance with activators at a temperature of 530…560 ºC during 2…3 hours. The nitriding process was carried out in the closed atmosphere in the chamber furnace without application of the protective atmospheres. Influence of laser pre-treatment and final nitriding on structure, thickness, phase structure, microhardness of surface layers of steel samples has been investigated. Results: It is shown that preliminary hardening by laser increases surface hardness in 0.88…1.15 times after nitriding, depending on brand of steel and speed of a laser beam movement, in comparison with steel nitriding in similar conditions. The combined treatment promotes significant increase in the strengthened layer – up to 0.49 mm for 40 steel type, up to 0.55 mm for 40Cr steel type and up to 0.65 mm for 38Cr2MoAl steel type.

Розробка нових ресурсозберігаючих і економічно доцільних технологій комбінованого зміцнення сталевих деталей із значним скороченням тривалості процесу є важливою і актуальною задачею. Мета: Метою роботи є розробка технології комбінованого зміцнення сталевих деталей для забезпечення високих експлуатаційних властивостей поверхневого шару сталі шляхом інтенсифікації процесу азотування за рахунок попередньої лазерної обробки поверхні сталевих виробів. Матеріали і методи: Матеріалом для дослідження є сталі марок 40, 40Х і 38Х2МЮА. Лазерну обробку сталей проводили на установці "ЛАТУС-31". Азотування проводили в середовищі дрібнодисперсної азотовмісної речовини з активаторами при температурі 530…560 ºC протягом 2…3 годин. Процес азотування проводили в закритій атмосфері в камерній печі без застосування захисних атмосфер. Було досліджено вплив попередньої лазерної обробки і кінцевого азотування на структуру, товщину, фазовий склад, мікротвердість поверхневих шарів зразків сталей. Результати: Показано, що попереднє лазерне зміцнення підвищує поверхневу твердість після азотування в 0,88…1,15 рази в залежності від марки сталі й швидкості переміщення лазерного променя в порівнянні з азотуванням сталей в аналогічних умовах. Комбінована обробка сприяє значному стовщенню зміцненого шару – до 0,49 мм для сталі марки 40, до 0,55 мм для сталі марки 40Х і до 0,65 мм для сталі марки 38Х2МЮА.
Поверхневе зміцнення сталевих деталей
Keywords: combined treatment; laser treatment; nitriding; surface hardness; thickness of the hardened layer; комбінована обробка; лазерна обробка; азотування; поверхнева твердість; товщина зміцненого шару